The reality of creativity at the basic stages in Jordanian private schools within the Arabic language curriculum in the light of my speaking and logical thinking skills from the point of view of the Arabic language teachers working there - Alshoara, Amal Madallah Mohammad (Technium Social Sciences Journal, 2023)
The current study aimed to identify the reality of creativity among the basic stages in the Jordanian private schools within the Arabic language curriculum in the light of my speaking skills and logical thinking from the point of view of the Arabic language teachers working there. The sample of the study consisted of (320) male and female teachers, who were selected in a stratified random manner. The descriptive survey method was used in the current study. To achieve the objectives of the study, a questionnaire was developed, and its validity and reliability were confirmed. The results showed that the reality of creativity among the basic stages in the Jordanian private schools within the Arabic language curriculum in the light of my skills of speaking and logical thinking from the point of view of the teachers of the Arabic language working in it was medium. The search results also showed that there are statistically significant differences at the level of significance (α ≤ 0.05) according to the gender variable in favor of the female category, and there are no statistically significant differences according to the educational qualification variable, and there are no statistically significant differences according to the years of experience variable. In the light of these results, the study recommended that the private education departments pay attention to the levels of creativity in the skills of logical thinking and speaking within the Arabic language curriculum for students of the basic stages, and to hold specialized courses and workshops for male and female teachers of the basic education stages to train them on ways to develop creativity.